Performance analysis of optical zero cross correlation in OCDMA system - Anuar, Mat Safar; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad; Saad, N.M.; Andonovic, I. (Asian Network for Scientific Information, 2009)
Link to publisher's homepage at http://www.scialert.net/index.php